X-Y Chromosom Bearing Sperm Proportion of Local Ram after Sexing with Different Combination of Bovine Serum Albumin (BSA) Concentration - Solihati, Nurcholidah; Rasad, Siti Darodjah; Hilmia, Nena; Winangun, Kikin; Toha, Toha (ANIMAL PRODUCTION, 2023)
The research aims to evaluate proportion of X-Y chromosom bearing sperm after sexing of local ram semen with different combination of BSA concentration. The research object was ten ejaculated semen of local ram, three years old. The research design used CRD (completely randomize design) with four treatments of BSA concentration combination on upper and bottom layer (T1: 3% & 6%, T2: 4% & 6%, T3: 5% & 10%, and T4: 6% & 12%), and 10 repetitions. Data analysis using analysis variance and Duncan’s Multiple Range Test. The result showed that combination of BSA concentration was significantly effect on proportion of X-Y chromosome bearing sperm of local ram sperm. The higher average proportion of X- and Y- chromosome bearing sperm was obtained at combination 5% (75.55±1.09% for X) at upper layer and 10% BSA (76.45±1.12% for Y) of bottom layer. The conclusion is that combination of BSA concentration significantly effect on proportion of X-Y chromosome bearing sperm, and concentration of 5% and 10% BSA at upper layer and bottom layer gave the higher proportion of X-Y chromosome bearing sperm of local ram sperm.